Assessment of radiological hazards in the phosphate mining area of Kpogamé, Togo. (June 2021) - Hazou, Eyakifama; Patchali, Tchilabalo E.
Abstract: Radioactive elements of natural origin are present everywhere in the environment as well as sediments in different concentrations depending on the local geology of soil. These elements are hazardous to the environment and to human health. This present work studied the radioactivity of a set of soil samples of phosphates tailings collected from a mining site in Kpogamé with a view to assessing the radiological hazards. Collected soil samples were analyzed at the Jožef Stefan Institute lab using high purity germanium detector, and radiological parameters such as radium equivalent, absorbed dose rate, indoor and outdoor annual effective dose rates, internal and external hazards indices, Gamma radiation representative level index and excess lifetime cancer risk for outdoor exposure were deducted. Higher values of activity concentrations were found for certain samples (values reaching 319.3 and 57.9 Bq/kg for Ra-226 and Th-232) when compared to UNSCEAR values. Higher values of these radiological parameters were also obtained when compared to the recommended limit and worldwide values (for example the maximum value of 176.10 ​nGy/h obtained for the absorbed dose rate was more than twice higher the worldwide average value of 84 ​nGy/h). Overall, five locations showed values above the norm. These locations have high values of excess lifetime cancer risk for outdoor exposure (0.3115×10 -3 – 0.7525×10 -3 ). The implication of these results is that there are locations around Kpogamé phosphate mining area with high probability of getting cancer from ionizing radiation associated to the environmental geology. Therefore, it is recommended to optimize the way to extract ores and avoid public to access the mining sites without knowing the level of radiation dose in this area.